TRANSITION AND POST-CONFLICT MACROECONOMIC POLICIES IN SERBIA - Labus, Miroljub (Economic Annals, 2020)
This paper evaluates the economic performance of the three distinct policy regimes that have been adopted in Serbia since the onset of transition in 2000. The conflict period from 1991 to 1999 deter-mined the starting point of transition and its subsequent realisation. This pre-transi-tion shock was more severe than the shock imposed by the Great Recession in 2008. Besides these shocks, the legacy of con-flict, and unresolved privatisation issues, macroeconomic policies also substantially influenced the performance of the Serbian economy. Three distinct policies were implemented between 2000 and 2018 with clearly differ-ent approaches: neoliberal, populist, and interventionist. This paper evaluates these policies using quarterly data on 20 macro-economic indicators classified in 5 groups: macroeconomic stability and domestic, foreign, financial, and labour markets. Re-garding the achievements of the three mac-roeconomic policies, the neoliberal policy is usually blamed for all the deficiencies in the economy in the period between 2000Q1 and 2006Q2. To the contrary, our data in-dicates that this policy performed the best. The populist policy in the next period from 2006Q3 to 2012Q2 performed the worst. Fi-nally, the interventionist policy, starting in 2012Q3 and evaluated up to 2018Q4, has been inferior to the neoliberal policy but superior to the populist policy. The analysis suggests that apart from macroeconomic policies the starting point of transition mat-ters for a successful economic transition.